Digital Press In The Era Of Disruption: Reconstructing The Legal Framework Toward Responsible Freedom Of Information In Indonesia - Lukman, Dian Arlesti; Djatmika, Prija; Sugiri, Bambang; Yuliati, Yuliati (KLAUSULA (Jurnal Hukum Tata Negara Adminitrasi Dan Pidana), 2026)
The era of digital technological disruption has structurally altered the press ecosystem in Indonesia. The presence of media entities operating online without established institutional infrastructure — academically termed "homeless media" — raises fundamental legal issues not yet adequately accommodated by Law Number 40 of 1999 on the Press. This research aims to analyze the legal framework for the digital press in Indonesia in the context of technological disruption, identify existing normative gaps, and formulate a legal framework reconstruction capable of realizing responsible freedom of information. This research employs a normative juridical method with four approaches: statutory, conceptual, historical, and comparative law. Comparative studies were conducted on the digital press regulatory systems of South Korea, the United Kingdom, Australia, and Germany. The findings identify five main normative gaps: (1) the absence of an inclusive definition of digital press legal subjects; (2) the inadequacy of online media verification mechanisms; (3) the weakness of digital journalist protection; (4) ambiguity in liability regimes; and (5) normative disharmony between the Press Law and the Electronic Information and Transactions Law (EIT Law). Legal reconstruction is required through a progressive legal paradigm that prioritizes the social function of the press over institutional formalism